The effect of Different Types of Orange Acid and Immersion Time on the Quality of Goldfish Naniura - Gina Mutiara Febrian; Elisa Julianti; Herla Rusmarilin (Universitas Sumatera Utara, 2016)
Naniura is one of Batak’s traditional food that made from fresh goldfish and soaked with orange acid and spices until the fish flesh soften, without any cooking process. The aim of this research was to find the best orange acid and immersion time in producing goldfish naniura with the best characteristic of microbiology, chemical, and sensory quality that can be accepted by consumers. Types of orange acid used were lime, rough lemon, calamondin, and kaffir lime. Immersion time were 4, 5, and 6 hours. The results showed that the interaction between different types of orange acid and immersion time had significant effect (P<0,05) on pH, total acid, and texture score. The increasing of immersion time increased the total acid, organoleptic value of texture, and texture score, but decreased the moisture content, protein content, total volatile nitrogen, pH, and total microbes. The goldfish naniura with the best quality (based on organoleptic value of flavor and texture, total volatil nitrogen, and protein content) was the treatment using lime with 5 hours immersion. Keywords : Goldfish naniura, lime, rough lemon, calamondin, kaffir lime, immersion time